Experimental study on the influence of wetting agent addition on the water adsorption and impact crushing dust generation of coal. Issue 5 (6th April 2022) - Zheng, Lei; Li, Dewen; Xu, Shengdong
Abstract: This study is aimed at investigating the influence of wetting agent addition on the water adsorption capacity, dust generation capacity and dust particle size distribution of coal. To achieve this aim, nonylphenol ethoxylate 10 wetting agent was used as an additive to prepare a 0.1% concentration solution, and a comparative test was conducted on different coal types from three coal mines in different provinces. The test results suggest that the natural saturated water adsorption time of coal was shortened by 33%–67% through wetting agent addition. Therefore, wetting agents are effective for enhancing water injection operations that require a limited construction period. The influence of wetting agent addition on the saturated water adsorption amount differed significantly for different coal types, and the wetting agent did not generally improve the saturated water adsorption rate. However, wetting agent addition alone did not lower the dust generation rate from coal. For a given moisture content, the wetting agent influenced the particle size distribution of dust generated during impact crushing differently between types of coal. For the three coal types investigated, wetting agent addition reduced the concentration of airborne by up to 8%.